Pendampingan Pembuatan dan Penerapan Standard Sanitation Operating Procedure dan Tata Letak Ruang Produksi pada Produksi Kerupuk Ikan Payus “Pamurbaya” Surabaya - Erliyanti, Nove; Putra, Andre Yusuf Trisna (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Standard Sanitation Operating Procedures (SSOP) and the production process layout play an essential role in food production so that product quality complies with standards and food safety. The problem faced by the partner (UD Sumber Rejeki) is that there is no SSOP and a good production space layout. This community service (PkM) aims to assist partners in making SSOP and production space layouts so that the products produced comply with quality and food safety standards. The methods used are the active participation approach (partners play an active role during PkM), the activity orientation approach (assisting partners in making SSOP and production space layout), and the SSOP implementation approach and production space layout. The result of this PkM is the enthusiasm and activeness of partners during assistance in making SSOP and layout of production space. Another result is the availability of SSOP and the layout of the production room, which is placed in the production room.